Expansion of the Emerging Fungal Pathogen Cryptococcus bacillisporus Into America: Linking Phylogenetic Origin, Geographical Spread and Population Under Exposure Risk - Carvajal, Jorge G.; Alaniz, Alberto J.; Carvajal, Mario A.; Acheson, Emily S.; Cruz, Rodrigo; Vergara, Pablo M.; Cogliati, Massimo (Frontiers in Microbiology, 2020)
In 2018 the fungal pathogen Cryptococcus bacillisporus (AFLP5/VGIII) was isolated for the first time in Chile, representing the only report in a temperate region in South America. We reconstructed the colonization process of C. bacillisporus in Chile, estimating the phylogenetic origin, the potential spread zone, and the population at risk. We performed a phylogenetic analysis of the strain and modelled the environmental niche of the pathogen projecting its potential spread zone into the new colonized region. Finally, we generated risk maps and quantified the people under potential risk. Phylogenetic analysis showed high similarity between the Chilean isolate and two clonal clusters from Californa, US and Colombia in South America. The pathogen can expand into all the temperate Mediterranean zone in central Chile and western Argentina, exposing more than 12 million people to this pathogen in Chile. This study has epidemiological and public health implications for the response to a potential C. bacillisporus outbreak, optimizing budgets, routing for screening diagnosis, and treatment implementation.